Impact of Operating Conditions on Fouling Probability and Cake Height in Ultrafiltration of Latex Solution - Abdelrasoul, Amira; Doan, Huu; Lohi, Ali (Journal of Membrane and Separation Technology, 2013)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The aim of the present study was to investigate the effects of operating conditions (transmembrane pressure, feed flow rate, and feed concentration) on the fouling attachment probabilities, mass of fouling, and cake height. Polycarbonate flat membrane with a pore size of 0.05 µm was used under a constant feed flow rate and cross-flow mode in ultrafiltration of a latex paint solution. The results obtained indicate that increasing transmembrane pressure from 15 to 45 psi lead to an increase in the particle-to-particle (αpp) and particle-to-membrane (αpm) attachment probabilities from 0.4 to 0.76 and 0.55 to 0.8, respectively. It was observed that both attachment probabilities were significantly decreased when the feed flow rate was increased from 1 to 6 LPM (cross flow velocity from 10.4 to 62.5 cm/s). As a consequence, mass of fouling and cake height were reduced. Increasing the feed concentration from 0.78 to 1.82 kg/m3 resulted in a substantial raise in the cake height from 4.3 to 18.5 µm. Response Surface Methodology (RSM) was used to set up the experimental design. According to regression analysis, two correlation models were obtained in order to predict the fouling attachment probabilities at different operation conditions. Estimated attachment probabilities were used to predict mass of fouling retained by membrane.